Pengembangan Sistem Informasi Penyewaan Lapangan Futsal Berbasis Website Di Garuda Futsal Dan Gor Futsal Kabupaten Bulukumba - Rifqhy Darmawan; Nurwahid Syam; Perawati Perawati (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to: (1) design a web-based Futsal Field Rental Information System at Garuda Futsal and GOR Futsal, Bulukumba Regency; (2) implement a web-based Futsal Field Rental Information System at Garuda Futsal and GOR Futsal, Bulukumba Regency; and (3) determine user responses toward the web-based Futsal Field Rental Information System at Garuda Futsal and GOR Futsal, Bulukumba Regency. The research employed the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of the study indicate that: (1) the futsal field rental process at Garuda Futsal and GOR Futsal, Bulukumba Regency, was previously carried out manually, resulting in problems such as schedule conflicts, rental data recording errors, and delays in information management; (2) the web-based Futsal Field Rental Information System was successfully designed using Unified Modeling Language (UML), including use case diagrams, activity diagrams, sequence diagrams, and class diagrams as the foundation for system development; (3) the system was successfully implemented as a website providing features for field management, scheduling, pricing management, membership management, transaction processing, reporting, customer reviews, and online field reservations. Based on the results of Black Box Testing, all system functions operated according to the specified requirements and were declared valid; and (4) user responses toward the system were highly positive, achieving a score of 90.9%, indicating that the developed system is feasible for use in supporting futsal field rental activities more effectively and efficiently.